Synthesis of New Heterocyclic Derivatives from Thiophenol and Evaluation their Biological Activity - Noor Y. Jaber (Journal of Global Pharma Technology, 2019)
S-Chloroacetyl thiophenol (A) was synthesized by reaction of thiophenol with chloroacetyl chlorid, then the product (A) was reacted with hydrazine hydrate to give hydrazide derivative (B), which was introduced in different synthetic methods to produce either Schiff bases derivatives or to produce heterocyclic compounds. All compounds were confirmed by their melting point, FT-IR spectra, 1H-NMR, 13C-NMR spectrum and studying the possibility for their application as antibacterial and antifungal agents to some of them.Keywords: Thiopohenol, Hydrazen hydrate, Schiff bases.